Gas Hydrates as a Means for Biogas and Biomethane Distribution - Moghaddam, Elham Ahmadi; Larsolle, Anders; Tidåker, Pernilla; Nordberg, Åke (Frontiers in Energy Research, 2021)
Biomethane is receiving great attention as a renewable energy gas with lower environmental impacts and diversified sources of production. However, availability of gas infrastructure is an important factor in biomethane development and use. Biomethane can be distributed by the natural gas or local biogas grid. Biomethane can also be road-transported as compressed biomethane (CBG) or liquefied bio-methane (LBG). Biomethane could be distributed via gas hydration technology, where methane molecules are physically trapped within the crystalline structures of frozen host water molecules as gas hydrate compounds. Using life cycle assessment methodology, this study compared the energy performance and climate impact of two gas hydrate scenarios, biogas hydrate and biomethane hydrate, with that of a base case distributing biomethane as CBG. The technical system, from biogas upgrading, hydration, compression and road transport to filling station of biomethane as CBG, was included in the analysis. Results of this study show that distribution of biomethane as gas hydrates had a lower energy performance and higher climate impact than compressed biomethane distribution. The low energy performance was due to high electricity demand in hydrate formation and dissociation processes. The gas hydrate scenarios also had higher climate impacts as a result of high methane losses from hydrate formation and dissociationdissociation and emissions related to energy source use. Biogas upgrading to biomethane also significantly contributed to methane losses and climate impact of the scenarios studied.